Obesity in pregnancy: a major healthcare issue. Issue 1020 (21st October 2010) - Tsoi, Elly; Shaikh, Humera; Robinson, Stephen; Teoh, Tiong Ghee
Abstract : The prevalence of maternal obesity is rising, up to 20% in some antenatal clinics, in line with the prevalence of obesity in the general population. Maternal obesity poses significant risks for all aspects of pregnancy. There are risks to the mother with increased maternal mortality, pre-eclampsia, diabetes and thromboembolic disorders. There is increased perinatal mortality, macrosomia and congenital malformation. The obstetric management, with increased operative delivery rate, and increased difficulty of anaesthesia, carry risk for the obese mother. Long term complications associated with maternal obesity include increased likelihood of maternal weight retention and exacerbation of obesity. This review aims to discuss these risks with a view to suggesting management to ensure the best outcome for both the mother and the offspring.